2001
DOI: 10.1007/bf02734048
|View full text |Cite
|
Sign up to set email alerts
|

Constraint, alcoholism, and electrodermal response in aversive classical conditioning and mismatch novelty paradigms

Abstract: This study investigated whether low levels of the personality trait of constraint and early-onset alcoholism would be associated with deficits in aversive conditioning and smaller responses to novelty in a stimulus mismatch protocol. Personality traits (constraint and socialization) and skin conductance responses (SCRs) during conditioning and novelty paradigms were assessed in alcoholics (n=41) and non-alcoholics (n = 32). The conditioning protocol involved measuring SCRs after conditioned stimuli (CS+: tones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The average intensities resulting from this were 3.96 mA (S.D. = 2.25) and thus similar to other experiments with painful stimuli (Finn et al, 2001).…”
Section: Methodsmentioning
confidence: 52%
“…The average intensities resulting from this were 3.96 mA (S.D. = 2.25) and thus similar to other experiments with painful stimuli (Finn et al, 2001).…”
Section: Methodsmentioning
confidence: 52%
“…Autonomic responses have been measured in studies of chronic alcoholics with mixed results ( Maltzman & Marinkovic, 1996 ). Some studies failed to find abnormalities in responsivity ( Wrase et al, 2002 ; Reid et al, 2006 ; Pomerleau et al, 1983 ), or have observed lower sensitivity and greater habituation in alcoholic participants compared to nonalcoholic controls ( Finn et al, 2001 ). In the present study, SCR results indicated lower sympathetic arousal levels in alcoholics, in agreement with previous reports of lower skin conductance orienting responses to novel stimuli in alcoholic Korsakoff patients ( Oscar-Berman & Gade, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the baseline level of SCR responsivity, SCRs were measured in response to the nonemotional stimulus, mismatch in sounds18 (12 of the PD patients and 6 of the NC subjects). We presented the two sets of eight sound stimuli (80 db SPL, intertrial interval varied between 11 and 19 s).…”
Section: Methodsmentioning
confidence: 99%